Listening to Foreign Languages: Pump Up the Volume - New, Boris; Guichet, Clément; Spinelli, Elsa; Barra, Julien (Journal of cognition, 2025)
In this study, we investigated whether the visual "word height superiority illusion" (New et al., 2016) could be found in the auditory modality. In two experiments, participants listened to a word-word or word-pseudoword pair of the same or different intensity and judged whether one was louder than the other. They judged stimuli from their native language (L1) and second language (L2). In Experiment 1 with native French speakers, we found that words were perceived louder than pseudowords in the L1 (French) and the L2 (English). Moreover, the illusion was stronger in the L1 (French) than in the L2 (English). In Experiment 2 with native English speakers, we replicated the illusion both in the L1 (English) and the L2 (French) but to a similar extent. Overall, we replicated the visual word height superiority illusion in the auditory modality, which suggests that this may reflect a more general cognitive mechanism.